2015
DOI: 10.1186/s12939-015-0251-2
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national comparison of socioeconomic inequalities in obesity in the United States and Canada

Abstract: IntroductionPrior cross-national studies of socioeconomic inequalities in obesity have only compared summary indices of inequality but not specific, policy-relevant dimensions of inequality: (a) shape of the socioeconomic gradient in obesity, (b) magnitude of differentials in obesity across socioeconomic levels and, (c) level of obesity at any given socioeconomic level. We use unique data on two highly comparable societies – U.S. and Canada - to contrast each of these inequality dimensions.MethodsData came fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 42 publications
(39 reference statements)
2
20
0
Order By: Relevance
“…In a recent analysis of data from 169 countries, income inequality was shown to be a greater predictor of average height than absolute national income 34. Our findings also provide further evidence in support of previous studies showing better health among people at all points in the social hierarchy in more equal countries 11–16…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In a recent analysis of data from 169 countries, income inequality was shown to be a greater predictor of average height than absolute national income 34. Our findings also provide further evidence in support of previous studies showing better health among people at all points in the social hierarchy in more equal countries 11–16…”
Section: Discussionsupporting
confidence: 89%
“…One previous ecological study using aggregated mortality data for rich and poor counties within US states found that mortality rates for some causes of death were lower for everyone in more equal US states, but for causes of death with no social gradient, there was no inequality effect 10. Several studies have used individual data to compare social gradients in health in different countries 11–17. When they are interpreted in relation to income inequality, they provide some indication that health is better among people at all points in the social hierarchy in more equal countries.…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic gradients in MetS components like obesity are less steep in Canada, when compared to countries that are culturally similar like the United States (43). It is possible that in societies with less pronounced health disparities, adverse experiences need to occur during sensitive or vulnerable periods for these effects to become manifest, but more cross-national research will be needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…That is, we are still unaware of these patterns at local levels. As states and locations may vary in the resources and how resources can operate (67)(68)(69), it is important to conduct local research on whether or not educational attainment, income, and employment generate similar or different health gain for non-Hispanic Blacks than non-Hispanic Whites. The results derived from such studies can potentially inform local policy on the most effective interventions that can equalize health across racial groups, particularly non-Hispanic Blacks and non-Hispanic Whites.…”
Section: Due To Multiple Societal Mechanisms Ses Indicators May Genementioning
confidence: 99%